Computational Aerodynamic Analysis Of Multicomponent Airfoil Using Viscous-Inviscid Interaction Scheme Nteraction Scheme [QA929. N818 2005 f rb]. - Haji Ismail, Noor Iswadi (2005)
Kajian ini telah dijalankan berdasarkan pengaplikasian tentang interaksi aliran likattak likat.